2003
DOI: 10.1038/sj.leu.2403040
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of tyrosine 393 in the kinase domain of Bcr-Abl influences the sensitivity towards imatinib in vivo

Abstract: The Bcr-Abl fusion protein arising through the t(9;22)(q34;q11) reciprocal translocation is the causative agent in chronic myeloid leukemia and a subset of acute lymphocytic leukemia. Imatinib mesylate is a specific inhibitor of the Bcr-Abl kinase and has shown promising results in clinical studies. The structural relation between the Bcr-Abl oncogene and the tyrosine kinase inhibitor imatinib has recently been elucidated by an elegant crystal structure analysis, emphasizing the importance of dephosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…52,53 The phosphorylation of BCR-ABL1 and JAK2 is reciprocal. Besides v-Src sarcoma (Schmidt-Ruppin A-2) viral oncogene homolog (SRC) kinase family members like v-yes-1 Yamaguchi sarcoma viral related oncogene homolog (LYN), [54][55][56][57][58] JAK2 is able to phosphorylate BCR-ABL1 on tyrosine residue 177. 52 This particular residue is critical for BCR-ABL1-induced disease maintenance as it allows binding of the SH2/SH3 domaincontaining growth factor receptor-bound protein 2 (GRB2) protein and the rat sarcoma (RAS)-activating nucleotide exchange factor son-of-sevenless (SOS), critical components of the pathway by which tyrosine kinases induce RAS activation.…”
Section: Bcr-abl1/jak2 Networkmentioning
confidence: 99%
“…52,53 The phosphorylation of BCR-ABL1 and JAK2 is reciprocal. Besides v-Src sarcoma (Schmidt-Ruppin A-2) viral oncogene homolog (SRC) kinase family members like v-yes-1 Yamaguchi sarcoma viral related oncogene homolog (LYN), [54][55][56][57][58] JAK2 is able to phosphorylate BCR-ABL1 on tyrosine residue 177. 52 This particular residue is critical for BCR-ABL1-induced disease maintenance as it allows binding of the SH2/SH3 domaincontaining growth factor receptor-bound protein 2 (GRB2) protein and the rat sarcoma (RAS)-activating nucleotide exchange factor son-of-sevenless (SOS), critical components of the pathway by which tyrosine kinases induce RAS activation.…”
Section: Bcr-abl1/jak2 Networkmentioning
confidence: 99%
“…For the methylcellulose assays, colonies were picked after 14 days and analyzed by flow cytometry. On average, 20 colonies were analyzed from each plate (range [15][16][17][18][19][20][21][22][23][24][25]. Generally, the colony number decreased with higher imatinib concentrations (data not shown) and revealed a strong selection of EGFP þ /Bcr-Abl mutant expressing cells upon addition of imatinib, whereas without imatinib there was no significant difference in the percentage of EGFP þ /Bcr-Abl mutant cells compared to the initially plated ratio (Figure 3c and d).…”
Section: Activity Ofmentioning
confidence: 99%
“…It has previously been shown that the bicistronic MIGRI vector which contains the MSCV retroviral LTR promoter followed by an IRES-EGFP cassette allows a slightly higher expression than the MSCV vector carrying a phosphoglycerate promoter driving a neomycin resistance gene. 22 The small difference in activity of the two MSCV-based vectors is thought to be caused by promoter competition in the MSCV-pgk-neo vector. For this reason, we expressed the Bcr-Abl mutants in the MIG-constructs to ensure expression of the Bcr-Abl mutants is at least as high as expression of the Bcr-Abl wt construct.…”
Section: Establishment Of a Competitive Repopulation Assaymentioning
confidence: 99%
See 2 more Smart Citations